Comparison of different cryotherapy recovery methods in elite junior cyclists - Chan, Yue-Yan (Asia Pac J Sports Med Arthrosc Rehabil Technol, 2016)
BACKGROUND/OBJECTIVE: Cold water immersion (CWI) and active recovery treatment (ACT) are commonly used recovery treatments for athletes between exercise bouts, but they are sometimes limited by space and availability of equipment in training and competition venues. Therefore, the purpose of this study was to determine whether cold compression therapy (CCT) would provide the same effect as CWI and ACT as an alternative option in a hot environment. METHODS: Eight elite male junior cyclists (age, 15.5 ± 1.2 years; height, 167.7 ± 3.3 cm; body mass, 57.3 ± 3.5 kg; peak oxygen uptake, 64.7 ± 4.3 mL/kg/min) completed a maximal cycling test to determine their peak power output (PPO) and oxygen uptake. Then they completed three tests using randomised recovery protocol of CWI, CCT and ACT for 15 minutes. Each test consisted of two 35-minute exercise bouts, with 5 minutes of warm-up, 15 minutes of cycling at 75% PPO and 15 minutes maximal trial. The two exercise bouts were separated by 60 minutes (5 minutes cool-down, 10 minutes preparation for recovery treatment, 15 minutes recovery treatment, and 30 minutes passive recovery). RESULTS: There was no significant difference between average power output, blood lactate, rating of perceived exertion, and heart rate for two time-trial bouts for all recovery treatments. A significant decrease in core temperature was noted prior to the start of the second exercise bout for CWI. CONCLUSION: CCT, CWI and ACT are all useful recovery treatments between exercise bouts.